The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4014/jmb.2106.06043
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Lysimachia christinae Hance Prevents Cholesterol Gallstone in Mice by Affecting the Intestinal Microflora

Abstract: With changes in human dietary patterns, the proportion of high-fat and high-cholesterol foods in the daily diet has increased. As a result, the incidence rate of cholelithiasis is increasing rapidly. Many studies have reported on the crucial role that the intestinal microflora plays in the progression of gallstones. Although the whole herb of Lysimachia christinae, a traditional Chinese medicine, has long been extensively used as a remedy for cholelithiasis in China, its effects on the intestinal microflora re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Chaihu Shugan reversed this change in gut microbiota composition to that observed in the control group in a dose-dependent manner. Lactobacillus can prevent CGS formation by fully activating the hepatic and ileal FXR signaling pathway ( Oh et al, 2021 ; Ye et al, 2022 ), and might be an active target bridge for other materials, such as Lysimachia christinae ( Liu et al, 2021 ), tea ( Huang et al, 2019 ), and coffee and caffeine ( Ishizuk et al, 2003 ; Khochapong et al, 2021 ), to prevent CGS function. Moreover, Lactobacillus and Akkermansia have been reported to be associated with high daily tea consumption-induced calcium oxalate renal calculi ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chaihu Shugan reversed this change in gut microbiota composition to that observed in the control group in a dose-dependent manner. Lactobacillus can prevent CGS formation by fully activating the hepatic and ileal FXR signaling pathway ( Oh et al, 2021 ; Ye et al, 2022 ), and might be an active target bridge for other materials, such as Lysimachia christinae ( Liu et al, 2021 ), tea ( Huang et al, 2019 ), and coffee and caffeine ( Ishizuk et al, 2003 ; Khochapong et al, 2021 ), to prevent CGS function. Moreover, Lactobacillus and Akkermansia have been reported to be associated with high daily tea consumption-induced calcium oxalate renal calculi ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A team directly studied the correlation between dietary structure and biliary microbiota in patients with gallstones and found that the abundance of specific microbiota is highly correlated with the intake of dairy products, several fibers, and fatty acids ( 92 ). The oral administration of an aqueous extract of the Chinese herb L. christinae is shown to improve intestinal microbiota disorder significantly, reduce gallstone formation, and restore histological morphology in mice with gallstones ( 93 ). Dietary behavior is highly correlated with intestinal flora and biliary tract flora, further affecting cholesterol and BA metabolism.…”
Section: Gut Microbiota and Gallbladder Principal Diseasesmentioning
confidence: 99%
“…In traditional Chinese medicine, it has been used to treat various ailments, such as inflammation, diarrhea, and jaundice. It has also been used to promote diuresis, in detoxification, and to alleviate pain [5]. In European traditional medicine, the plant has been used as an astringent, diuretic, and expectorant.…”
Section: Introductionmentioning
confidence: 99%